Comparative Analysis of Physicochemical Properties and Microbial Composition in High-Temperature Daqu With Different Colors - Deng, Ling; Mao, Xiang; Liu, Dan; Ning, Xin-Qiang; Shen, Yi; Chen, Bo; Nie, Hong-Fang; Huang, Dan; Luo, Hui-Bo (Frontiers in Microbiology, 2020)
High-temperature Daqu, also called Jiang-flavor Daqu, is the saccharifying and fermenting agent for brewing Jiang-flavor Baijiu. During the spontaneous solid-state fermentation of high-temperature Daqu, variations in temperature and moisture lead to microbial diversity and various metabolites, contributing to the distinct colors of high-temperature Daqu (referred to as white Daqu, black Daqu, yellow Daqu, and red Daqu). We aimed to investigate the differences in microbial communities, physicochemical indices, and potential functions among different high-temperature Daqu with distinct colors (labeled as QW, QB, QY, and QR) by amplicon sequencing. We found that Kroppenstedtia, Bacillus, and Thermoascus were predominant in all samples; Saccharopolyspora and Thermomyces were predominant in QB and QR; and Unclassfied_O_Eurotiales were predominant in QY. The results on the physicochemical characteristics indicated that compared with other Daqu samples, QW exhibited higher protease activity and lower acidity, whereas QB showed the opposite results. QR had the highest esterification yield, and QY exhibited the highest saccharification but lowest esterification yield.Functional prediction demonstrated that the higher abundances of genes encoding bacterial enzymes of QW and QY were related to the considerably higher abundances of Kroppenstedtia in QW (59%) and QY (87%), respectively. The highest abundance of Thermomyces in QB (80%) contributed to the highest abundance of genes encoding fungal enzymes in QB. This study revealed the microbial and functional dissimilarities of color-based high-temperature starters and helped facilitate the liquor fermentation process.